Why has the British national minimum wage had little or no impact on employment? - Metcalf, David (London, 2007)
"A century has passed since the first call for a British national minimum wage (NMW). That remarkable Fabian tract discussed wage setting, coverage, monopsony, international labour standards, inspection and compliance and the interaction between the NMW and the social security system. The NMW was finally introduced in 1999. It has raised the real and relative pay of low wage workers, narrowed the gender pay gap and now covers around 1-worker-in-10. The consequences for employment have been extensively analysed using information on individuals, areas and firms. There is little or no evidence of any employment effects. The reasons for this include: an impact on hours rather than workers; employer wage setting and labour market frictions; offsets via the tax credit system; incomplete compliance; improvements in productivity; an increase in the relative price of minimum wage-produced consumer services; and a reduction in the relative profits of firms employing low paid workers. "